2006
DOI: 10.1002/dys.322
|View full text |Cite
|
Sign up to set email alerts
|

Deficient morphological processing in adults with developmental dyslexia: another barrier to efficient word recognition?

Abstract: Research on dyslexia has focused on the phonological level of linguistic analysis. Here we extend the investigation of the linguistic competence of individuals with dyslexia to the morphological level of linguistic analysis. We examine whether adult Hebrew readers with dyslexia extract and represent morphemic units similarly to normal readers. Using the priming paradigm in the word fragment completion task, we measured the magnitude of morphological priming and contrasted this effect with the repetition primin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 70 publications
9
53
0
Order By: Relevance
“…Thus, few studies have been conducted on morphological knowledge (using both explicit morphological awareness tasks and implicit morphological processing tasks) among university students with dyslexia and even fewer have investigated morphological awareness specifically. To our knowledge, only two of the existing studies were conducted in an alphabetic writing system (for the English orthography, see Law, Wouters, and Ghesquière, 2015; for the French orthography, see Martin, Frauenfelder, and Colé, 2013), and two examined Hebrew-speaking university students with dyslexia (Leikin & Zur Hagit, 2006;Schiff & Raveh, 2007). Furthermore, although some other studies have assessed morphological awareness in English (e.g., Tractenberg, 2002;Leong, 1999), these studies examined populations with learning disabilities, including participants who presented with deficits other than developmental dyslexia.…”
Section: Phonological and Morphological Knowledge In Dyslexic Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, few studies have been conducted on morphological knowledge (using both explicit morphological awareness tasks and implicit morphological processing tasks) among university students with dyslexia and even fewer have investigated morphological awareness specifically. To our knowledge, only two of the existing studies were conducted in an alphabetic writing system (for the English orthography, see Law, Wouters, and Ghesquière, 2015; for the French orthography, see Martin, Frauenfelder, and Colé, 2013), and two examined Hebrew-speaking university students with dyslexia (Leikin & Zur Hagit, 2006;Schiff & Raveh, 2007). Furthermore, although some other studies have assessed morphological awareness in English (e.g., Tractenberg, 2002;Leong, 1999), these studies examined populations with learning disabilities, including participants who presented with deficits other than developmental dyslexia.…”
Section: Phonological and Morphological Knowledge In Dyslexic Studentsmentioning
confidence: 99%
“…The main characteristic of the morphological structure of words is that phonology and morphology are generally not dissociable. Although Schiff and Raveh (2007) found some weakness in morphological awareness in dyslexic students in Hebrew, Leiken and Zur Hagit (2006) showed that the contribution of morphological awareness to decoding was significant even after phonological processing was partialled out, suggesting that morphological awareness is an important factor in addition to phonological skills for successful word decoding.…”
Section: Phonological and Morphological Knowledge In Dyslexic Studentsmentioning
confidence: 99%
“…Using a morphological analogy task, Schiff and Ravid (2007) showed that Hebrew-speaking adults with dyslexia performed at a fourthgrade level and had more associative responses than fourth graders, testifying to the reduced morphological abilities of individuals with dyslexia. Two priming studies in Israel (Raveh & Schiff, 2008;Schiff & Raveh, 2006) revealed that, compared to control groups matched on chronological age or on reading age, adults with dyslexia responded as well as the controls to auditory morphological stimuli but not to visual ones during word recognition. Likewise, Ben-Dror et al (1995) found that Hebrew-speaking elementary school children with severe reading problems exhibited inferior morphological performance compared to both age-control and reading-control groups.…”
mentioning
confidence: 98%
“…Readers with RD have difficulties in reading morphologically complex words and make morphological errors in writing (Carlisle, 1987;Egan & Pring, 2004;Johnson & Grant, 1989;Moats, 1996;Schiff & Raveh, 2006;Worthy & Vise, 1996). Individuals with RD have low sensitivity to morphological elements such as the root and the pattern and show weaknesses in consciously extracting a morpheme and constructing another morphologically complex word.…”
mentioning
confidence: 99%
“…Grammatical awareness, often conceptualised as morphological awareness, has been tested in numerous ways, most often in children (e.g., Carlisle, 1995;Nunes, Bryant, & Bindman, 1997;Rubin, 1988), or in adults with dyslexia (e.g., Schiff & Raveh, 2007). Some studies have shown that at least in children, better grammatical awareness is related to stronger ability to read and spell grammatically complex words (e.g., Hauerwas & Walker, 2003;Nunes et al, 1997).…”
mentioning
confidence: 98%